THE IMAGE OF A PERSON WITH DISABILITY IN FAIRY TALES AND FINE ART AS A REFLECTION OF THE ATTITUDE OF THE SOCIETY - Gudonis, Vytautas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article, referring to the analysis of 36 fairy tales and fine art reproductions, attempts to decode the attitude of the society towards people with disabilities, their social status and potential opportunities. This topic has not been analysed from this aspect neither by philologists nor by the authors of special psychology. In fairy tales and examples of fine art the variety of attitudes towards people with disabilities has been encountered. A wide range of attitudes – from empathy to undisguised negative attitude – has been encountered.